KARAKTERISTIK KOMPON KARET PAVING BLOCK DARI LIMBAH KARET SKIM BERBAHAN PENGISI PASIR KUARSA - Aprillena Tornadez Bondan; Rahmaniar Rahmaniar (Jurnal Dinamika Penelitian Industri, 2018)
The aim of this research was to know the characteristic of paving block rubber which made from skim rubber waste as the main material, the quartz sand as the filler, and also get its formulation. The raw material used in the research was skim rubber waste 100 phr. This research used Completed Randomized Design (CRD) with 2 factorials. The first factor was the size of quartz sand (A) with the variations, respectively: A1= 200 mesh , A2=  400 mesh. The second factor was quartz sand concentration (B), respectively: B1= 50 phr, B2= 60  phr, B3 = 70 phr, B4= 80 phr. Quality testing for the characteristics of a rubber compound  were tensile strength, elongation at break, ozone resistance and volume changing. The quality testing results showed that the value of the physical characteristics of the compound with the best treatment results were the formula 6, which used skim rubber waste 100 phr, quartz sand size 400 mesh with concentration 60 phr. The test result value of tensile strength was 560 N/cm3, elongation at break  was 40%, ozone resistance  was no crack, and volume changing in SAE oil 40 at 70oC for 72 hours was 17,97%.